THE SEMANTIC DOMAIN AND UNDERSTANDING OF SPECIALIZED TEXTS IN LAW STUDENTS OF THE AMAZON NATIONAL UNIVERSITY OF MADRE DE DIOS - Béjar Ramos, Carlos (2020)
The research set out to determine the relationshipbetween the semantic domain and the comprehensionof specialized texts in students of the ProfessionalCareer of Law of the National Amazonian Universityof Madre de Dios. It is a study of a basic type, fordeveloping theoretical scientific knowledge regardingsemantics and reading comprehension of lesser andgreater academic complexity. It is descriptive level andcorrelational design. The sample was made up of 60students. The technique applied to collect the data wasevaluation and as an instrument a test was applied todetermine the semantic domain and the reading cardsto assess the levels of comprehension of specializedtexts. The semantic domain was broken down intodimensions of: vocabulary in context, synonym andantonym in context, paronym, paronym, homonyms,hyperonyms-hyponyms and textual markers. Thedimensions of text comprehension: comprehensionat the propositional level, local level, global level andelaborative level. The result was a correlation coefficientof (0.629) considered an average positive relationshipbetween variables in the sample and the studypopulation. It was concluded that there is a direct andsignificant relationship between the semantic domainand the understanding of specialized texts; the greaterthe semantic domain, the greater the understanding oftexts.